2012
DOI: 10.1371/journal.pone.0032332
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Sardinian Cave Salamanders (Genus Hydromantes) Is Mainly Determined by Geomorphology

Abstract: Detecting the factors that determine the interruption of gene flow between populations is key to understanding how speciation occurs. In this context, caves are an excellent system for studying processes of colonization, differentiation and speciation, since they represent discrete geographical units often with known geological histories. Here, we asked whether discontinuous calcareous areas and cave systems represent major barriers to gene flow within and among the five species of Sardinian cave salamanders (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 69 publications
1
51
0
1
Order By: Relevance
“…In recent years, phylogeographic studies have used genetic and molecular methods for investigating the history of the distribution of various taxa of amphibians (among others: Duellman 1999; Riberon et al 2001;Zeisset and Beebee 2001;Bonnet and Chippindale 2004;Vences et al 2004;Alexandrino et al 2007;Crottini et al 2007;Recuero et al 2007;Vences and Wake 2007;Stöck et al 2008;Shepard and Burbrink 2009;Mattoccia et al 2011;Chiari et al 2012). As far as Europe is concerned, Rana temporaria has been the subject of several papers (Veith et al 2003;Palo et al 2004;Gómez and Lunt 2006;Zeisset and Beebee 2008;Teacher et al 2009;Stefani et al 2012), probably because its current broad range (Gasc et al 1997;Kuzmin 1999;Sillero et al 2014) and the fact that it is adapted to relatively cold environments render this species a good model for evaluating the range changes that occurred during and after the Pleistocene coolings.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, phylogeographic studies have used genetic and molecular methods for investigating the history of the distribution of various taxa of amphibians (among others: Duellman 1999; Riberon et al 2001;Zeisset and Beebee 2001;Bonnet and Chippindale 2004;Vences et al 2004;Alexandrino et al 2007;Crottini et al 2007;Recuero et al 2007;Vences and Wake 2007;Stöck et al 2008;Shepard and Burbrink 2009;Mattoccia et al 2011;Chiari et al 2012). As far as Europe is concerned, Rana temporaria has been the subject of several papers (Veith et al 2003;Palo et al 2004;Gómez and Lunt 2006;Zeisset and Beebee 2008;Teacher et al 2009;Stefani et al 2012), probably because its current broad range (Gasc et al 1997;Kuzmin 1999;Sillero et al 2014) and the fact that it is adapted to relatively cold environments render this species a good model for evaluating the range changes that occurred during and after the Pleistocene coolings.…”
Section: Introductionmentioning
confidence: 99%
“…q This paper was edited by the Associate Editor Alfried Vogler. 76 speciation (Gavrilets, 2003 (Chiari et al, 2012;Howarth, 1996b for biogeographic studies as dispersal-limited lineage-in some 130 species the same individual has been observed on the same tree 131 over the course of months or even years (Weygoldt, 2000), though 132 such site fidelity has not been studied in Phrynus-that has both 133 epigean and cave taxa that tend to be restricted to single biogeo-134 graphic regions (Harvey, 2003 Vieques islands are highly distinct and unique and fall out as sister 336 to the remaining taxa in the analysis (Fig. 4).…”
mentioning
confidence: 99%
“…Genetic diversity, in terms of haplotype diversity (h) and nucleotide diversity (π), was found to be lower in H. amjiensis compared to other salamanders [e.g., Hydromantes (Chiari, et al, 2012); Hynobius tokyoensis (Matsui, et al, 2007); Salamandrella keyserlingii, (Malyarchuk, et al, 2010)]. The loss of genetic diversity could be susceptible to stochastic processes within H. amjiensis if these populations have recently undergone a reduction in their effective population size.…”
Section: Genetic Diversity In Hynobius Amjiensismentioning
confidence: 99%